Integrated management of childhood illness in Rwanda: Impact of mentorship on the quality of care in Nyanza and Huye districts - Alain Mirindi; Assumpta Mwali Kayinamura; Amedee Fidele Ndibaza; Liliane Uwamahoro; Dieudonne Ndatimana; Ferdinand Bikorimana; Christian Mazimpaka; Richard Kalisa (Wiley, 2024)
Abstract Background In Rwanda, health posts (HPs) are intermediary primary care facilities that provide comprehensive primary care services to communities and are located at a reasonable walking distance from people's homes. We assessed the readiness of HPs for Integrated Management of Childhood Illness (IMCI) services and examined changes in the quality of care for IMCI services between districts that implemented IMCI mentorship program (Nyanza district) and Huye district which it did not. Methods We conducted a prospective cohort study to assess whether there was change in the quality of IMCI care provided at 17 Nyanza HPs 1‐year after IMCI mentorship implementation. The readiness of HPs for IMCI was assessed across nine factors, resulting in essential (all factors) and desirable (less than seven factors) composite scores. Unpaired t‐tests were used to measure changes in IMCI quality. Results The HPs with IMCI mentorship had an increase in mean desirable (0.7-0.89) and essential (0.61-0.78) composite scores compared to non‐mentored HPs in Huye. The nurses who received mentorship program had improved scores in factors like IMCI training, service package availability, register availability, supportive supervision, and basic equipment availability. Quality improvements in IMCI assessments were observed in vital sign registration, danger sign detection, cough identification, malnutrition screening, and tuberculosis sign identification in the mentored HPs. Conclusion Mentorship of nurses in HPs holds promise for enhancing facility readiness and IMCI service quality. Before expanding clinical mentorship, identified gaps such as staffing, supply chains, and health financing need to be addressed.